Sukces typu instant – tożsamosc celebryty i celebutantki - Mazurek-Lipka, Olga (Kultura-Społeczeństwo-Edukacja, 2013)
Article Instant success – the identity celebrty and celebutante characteristic phenomenon is an attempt to quick success of media, which as celebrity and celebutante are the product. World media is not enough that distorts reality, creating new quality and seeks to take control over the creation of the trends that will be imitated. Contemporary culture is the essence of the theory of instant acceleration. Once success won years, now it has to be fast and spectacular. All items should be at the highest level of living. They hope the excitement and satisfaction of curiosity , once implemented through a keyhole or a glass against the wall. Today, the media have taken over this role perfectly showing the viewer to a world that has so far been elusive. The result of such activities is the creation of a new type of well-known public gures – celebrity. This is a person famous for being famous. This article is an attempt to de ne the characteristics of the phenomenon of celebrity and distinction. Its derivative is celebutante – coming home from a famous young woman who was interested in their lifestyle media and audience. Yes celebutante as celebrities are famous for being famous as long as possible trying to be popular selling. The essence of this phenomenon is the selling of the media elements of his private life – images of important events, interviews concerning the private sphere or frequenting the red carpet. It is also lending his name to promote different products or services. However, both celebrities and celebutantki are an extremely important part of contemporary reality and also they have a huge impact on the life of an ordinary man – a participant of the media.